2019
DOI: 10.1111/are.13963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary n-3HUFA on juvenile white shrimp, Litopenaeus vannamei: Growth, feed utilization, antioxidant enzymes activities and fatty acid compositions

Abstract: Present study investigates the effects of n-3 high-unsaturated fatty acid (n-3HUFA) levels on growth performance, antioxidant enzymes activities and fatty acid compositions of juvenile Litopenaeus vannamei. These represented seven iso-nitrogenous and iso-lipidic diets. Analysed n-3HUFA concentrations were 0.16% (control), 0.48%, 0.74%, 1.39%, 2.39%, 2.92% and 3.44% respectively. A total of 840 juvenile L. vannamei were randomly stocked into 21 0.5 m 3 tanks for 56 days. A significant increase (p < 0.05) was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…In the present study, WG and SGR showed at first an increasing and then a decreasing trend with increased dietary n-3 LC-PUFA level regardless of dietary lipid level, and the best growth performance was observed in crabs fed diets containing 19•8 and 13•2 mg/g dietary n-3 LC-PUFA at 7 and 12 % lipid, respectively. The results indicated that excessive dietary n-3 LC-PUFA levels led to detrimental effects on growth performance of S. paramamosain, which was in agreement with previous studies in L. vannamei (4) and Penaeus monodon (29) . A hypothesis put forward to explain this negative effect was the possibility that excessive levels of dietary LC-PUFA, which have higher susceptibility to peroxidation, would result in oxidative stress (30) .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, WG and SGR showed at first an increasing and then a decreasing trend with increased dietary n-3 LC-PUFA level regardless of dietary lipid level, and the best growth performance was observed in crabs fed diets containing 19•8 and 13•2 mg/g dietary n-3 LC-PUFA at 7 and 12 % lipid, respectively. The results indicated that excessive dietary n-3 LC-PUFA levels led to detrimental effects on growth performance of S. paramamosain, which was in agreement with previous studies in L. vannamei (4) and Penaeus monodon (29) . A hypothesis put forward to explain this negative effect was the possibility that excessive levels of dietary LC-PUFA, which have higher susceptibility to peroxidation, would result in oxidative stress (30) .…”
Section: Discussionsupporting
confidence: 92%
“…The result observed in the present study was different to those obtained in P. trituberculatus (initial weight 2•17 and 24•00 g, respectively) (10,11) where the optimum n-3 LC-PUFA requirement was 23•5 and 23•3 mg/g of diet when the dietary lipid was sufficient and DHA:EPA ratios were 0•9 and 1•1, respectively. Different results were also observed in other crustaceans, including Chinese mitten crab (E. sinensis), tiger shrimp (P. monodon), giant freshwater prawn (Macrobrachium rosenbergii) and L. vannamei (4,(33)(34)(35) , which suggested that the optimum n-3 LC-PUFA requirement varies with species, development stages, dietary lipid level, dietary DHA:EPA ratio and feed formulation. On the other hand, the optimal n-3 LC-PUFA level decreased from 20•1 to 12•7 mg/g as dietary lipid level increased from 7 to 12 % in the present study, which showed that .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The study presented here showed that the variation trend of CHOL and LDL was consisted with the reports mentioned above; however, TG and HDL did not show this similarity. A previous study from our group investigated the effects of dietary n‐3HUFA on serum biochemical indices of juvenile L. vannamei , and the result showed that CHOL, TG and LDL decreased with dietary n‐3HUFA increase, while HDL elevating (Yang et al, ). This discrimination cannot be explained without additional data.…”
Section: Discussionmentioning
confidence: 99%